Design of two ongoing clinical trials of tolvaptan in the treatment of pediatric patients with autosomal recessive polycystic kidney disease - Djalila Mekahli; Max C. Liebau; Melissa A. Cadnapaphornchai; Stuart L. Goldstein; Larry A. Greenbaum; Mieczyslaw Litwin; Tomas Seeman; Franz Schaefer; Lisa M. Guay-Woodford (BMC Nephrology, 2023)
Abstract Purpose Autosomal recessive polycystic kidney disease (ARPKD) is a hereditary condition characterized by massive kidney enlargement and developmental liver defects. Potential consequences during childhood include the need for kidney replacement therapy (KRT). We report the design of 2 ongoing clinical trials (Study 204, Study 307) to evaluate safety, tolerability, and efficacy of tolvaptan in children with ARPKD. Methods Both trials are of multinational, multicenter, open-label design. Age range at enrollment is 28 days to < 12 weeks in Study 204 and 28 days to < 18 years in Study 307. Subjects in both studies must have a clinical diagnosis of ARPKD, and those in Study 204 must additionally have signs indicative of risk of rapid progression to KRT, namely, all of: nephromegaly, multiple kidney cysts or increased kidney echogenicity suggesting microcysts, and oligohydramnios or anhydramnios. Target enrollment is 20 subjects for Study 204 and ≥ 10 subjects for Study 307. Results Follow-up is 24 months in Study 204 (with optional additional treatment up to 36 months) and 18 months in Study 307. Outcomes include safety, tolerability, change in kidney function, and percentage of subjects requiring KRT relative to historical data. Regular safety assessments monitor for possible adverse effects of treatment on parameters such as liver function, kidney function, fluid balance, electrolyte levels, and growth trajectory, with increased frequency of monitoring following tolvaptan initiation or dose escalation. Conclusions These trials will provide data on tolvaptan safety and efficacy in a population without disease-specific treatment options. Trial registration Study 204: EudraCT 2020–005991-36; Study 307: EudraCT 2020–005992-10.